The Role of Digital Financial Literacy in Moderating the Influence of Digital Payments on Overspending Behavior Among Generation Z in Surabaya - Kaisya Dinsa Novfrida; Ira Wikartika; Fani Khoirotunisa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine how perceived ease of use and perceived usefulness of digital payment systems influence overspending behavior among Generation Z in Surabaya, with digital financial literacy as a moderating variable. The study employed a quantitative approach using a survey method. Data were collected from 151 Generation Z respondents residing in Surabaya who actively use digital /payment systems. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to test the relationships between variables. The findings reveal that both perceived ease of use and perceived usefulness have a significant positive effect on overspending behavior. Furthermore, digital financial literacy moderates these relationships, reducing the tendency of overspending by enhancing financial awareness and self-control in digital transactions. The results highlight the importance of strengthening digital financial literacy among young consumers to ensure sustainable digital financial behavior. Policymakers, fintech firms, and educators can use these findings to design educational programs that promote responsible financial habits, supporting broader economic stability and inclusive digital growth.